Associations between mothers' and daughters' physical activity behavior, motivation, and body image perceptions: A multi-method study. - Thom, Julie D. (University of Ottawa (Canada), 2001)
The purpose of this thesis was to examine the associations among mothers' and daughters' physical activity behavior, motivation and body image perceptions using a multi-method approach. Phase 1 of this study was quantitative, and served to investigate the relationships between mothers' and daughters' physical activity behavior and motivation. Social Learning Theory (Bandura, 1977) and the Deviancy Model (Jessor & Jessor, 1977) were both used in order to investigate mother-daughter activity behaviors. For Phase 1, three groups were established based on the mothers' scores from the questionnaire: non-, moderate and high frequency exercisers. In order to further examine the mother-daughter relationship and specifically to investigate body image perceptions, a second qualitative phase (Phase 2) was conducted. Phase 2 consisted of interviewing 10 mothers and daughters (5 mother-daughter pairs). For this phase, a semi-structured interview guide was developed to further assess motivation and body image perceptions of both the mothers' and daughters'. Also, a Body Esteem Scale (Mendelson, White & Mendelson, 1997--98) was administered to the interviewees before conducting the interview. (Abstract shortened by UMI.)
Keywords: Psychology, Behavioral.